NaFeSnO4: Tunnel structured anode material for rechargeable sodium-ion batteries - Deu S. Bhange; Daniel A. Anang; Ghulam Ali; Jae-Ho Park; Ji-Young Kim; Jee-Hwan Bae; Woo Young Yoon; Kyung Yoon Chung; Kyung-Wan Nam (Electrochemistry Communications, 2020)
Nanorod-shaped NaFeSnO4 having a tunnel-structure analogous to CaFe2O4 is proposed as a novel anode material for rechargeable sodium-ion batteries. The material shows a considerably high charge capacity of 179 mAhg−1 with low redox voltages, decent rate, and cycling performance. XANES results reveal Fe3+/Fe2+ as the active redox couple associated with the sodium insertion/extraction during cycling.